Autotrophic and heterotrophic contributions to short-term soil CO 2 efflux following simulated summer precipitation pulses in a Mediterranean dehesa - Casals, Pere; Lopez-Sangil, Luis; Carrara, Arnaud; Gimeno, Cristina; Nogués, Salvador (Global Biogeochemical Cycles, 2011)
Autotrophic and heterotrophic components of soil CO2 efflux may have differential responses to environmental factors, so estimating the relative contribution of each component during summer precipitation pulses is essential to predict C balance in soils experiencing regular drought conditions. As even small summer rains induced high instantaneous soil respiration rates in Mediterranean wooded grasslands, we hypothesized that standing dead mass, surface litter, and topsoil layer could play a dominant role in the initial flush of CO2 produced immediately after soil rewetting; in contrast, soil CO2 effluxes during drought periods should be mostly derived from tree root activity. In a grazed dehesa, we simulated four summer rain events and measured soil CO2 efflux discontinuously, estimating its d 13 C through a Keeling plot nonsteady state static chamber approach. In addition, we estimated litter contribution to soil CO2 efflux and extracted soil available C fractions (K2SO4‐extracted C and chloroform‐fumigated extracted C). The d 13 C‐CO2 from in‐tube incubated excised tree roots and rewetted root‐free soil was −25.0‰ (±0.2) and −28.4‰ (±0.2), respectively. Assuming those values as end‐members’ sources, the autotrophic component of soil CO2 efflux was dominant during the severe drought, whereas the heterotrophic contribution dominated from the very beginning of precipitation pulses. As standing dead mass and fresh litter contribution was low (<25%) in the first day and negligible after, we concluded that CO2 efflux after rewetting was mostly derived from microbial mineralization of available soil organic C fractions.
Keywords: d13C; Drought; precipitation manipulation (voyant); Soil CO2 efflux

Root decomposition in grazed and abandoned dry Mediterranean dehesa and mesic mountain grasslands estimated by standard labelled roots - Casals, Pere; Garcia-Pausas, Jordi; Montané, Francesc; Romanyà, Joan; Rovira, Pere (Agriculture, Ecosystems & Environment, 2010)
Because root turnover represents the major source for building up soil organic matter in ecosystems with high belowground allocation, like grasslands, sensitive analyses on root decomposition rates may contribute to point out the effect of grazing abandonment on soil C and N dynamics. The objective was to detect changes in root C and N mineralization due to pasture abandonment in Mediterranean dehesa mountain grasslands. Root decomposition was estimated by ﬁeld incubation of 13 C- and 15 N-labelled wheat roots mixed with unlabelled soil over one year at 5 cm depth in grazed and short-term excluded grasslands in three contrasting situations: (i) a Mediterranean dehesa, (ii) altimontane and (iii) subalpine sites. In addition, the long-term effect of grazing abandonment was estimated in a subalpine shrub encroached site. Overall, root decomposition rates decrease from Mediterranean to mountain sites. Moreover, on mountain sites, either grazing exclusion or shrub encroachment reduced 13 C losses from root–soil bags in about four to seven percentage units; in contrast, such an effect was not detected in the Mediterranean grassland. The dynamics of 15 N derived from root–soil bags was site-dependent without a clear pattern related to site climate or grazing abandonment. In general, the fate of mineralized root-N, leached or immobilized in the surrounding soil, seems to be related to soil variables such as the C:N ratio.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: 13C; 15N; Grazing exclusion; Shrub encroachment; Subalpine grasslands; Tracer techniques

Soil CO2 efflux and extractable organic carbon fractions under simulated precipitation events in a Mediterranean Dehesa - Casals, Pere; Gimeno, Cristina; Carrara, Arnaud; Lopez-Sangil, Luis; Sanz, MJosé (Soil Biology and Biochemistry, 2009)
The magnitude of CO2 efﬂux pulses after rewetting a dry soil is highly variable and the factors regulating these pulses are poorly understood. In this ﬁeld experiment, we aimed to study the C dynamics after simulated summer rainstorms in a Mediterranean open holm oak woodland (dehesa). We hypothesized that because the herbaceous cover is mostly dead during the summer in this ecosystem, the short-term CO2 efﬂux (SR) after rewetting could mainly be explained by different measurable soil C fractions: i) K2SO4-extracted soil C (EOC); ii) microbial biomass C (MBC); or iii) chloroform-fumigated extracted C (CFE). On both grazed and abandoned dehesa sites, we simulated three summer rain events at two-week intervals and we measured SR discontinuously in three plots under tree canopy and in another three plots in open grassland. In each plot, C fractions and water content were estimated before (2 h) and after (36 h) each irrigation event. Following rewettings, SR increased up to ten times compared with nonirrigated plots. The CFE actually increased after rewetting in the ﬁrst two irrigations but not in the third event, suggesting that the capacity of the soil to release labile organic C from soil aggregates or litter was reduced after each irrigation event. Overall, the C released as CO2 in the ﬁrst 24 h was related to the CFE existing before rewetting, which may help to explain the spatial variability in SR. However, the explained variability decreased after each irrigation, suggesting a change to a less labile composition of the CFE fraction as a consequence of multiple drying-rewetting cycles
Keywords: Chloroform-fumigation K2SO4-extraction; drying-rewetting cycles; holm oak savanna woodland; Soil C fractions; Soil respiration

Soil CO2 efflux and extractable organic carbon fractions under simulated precipitation events in a Mediterranean Dehesa - Casals, Pere; Gimeno, Cristina; Carrara, Arnaud; Lopez-Sangil, Luis; Sanz, MJosé (Soil Biology and Biochemistry, 2009)
The magnitude of CO2 efﬂux pulses after rewetting a dry soil is highly variable and the factors regulating these pulses are poorly understood. In this ﬁeld experiment, we aimed to study the C dynamics after simulated summer rainstorms in a Mediterranean open holm oak woodland (dehesa). We hypothesized that because the herbaceous cover is mostly dead during the summer in this ecosystem, the short-term CO2 efﬂux (SR) after rewetting could mainly be explained by different measurable soil C fractions: i) K2SO4-extracted soil C (EOC); ii) microbial biomass C (MBC); or iii) chloroform-fumigated extracted C (CFE). On both grazed and abandoned dehesa sites, we simulated three summer rain events at two-week intervals and we measured SR discontinuously in three plots under tree canopy and in another three plots in open grassland. In each plot, C fractions and water content were estimated before (2 h) and after (36 h) each irrigation event. Following rewettings, SR increased up to ten times compared with nonirrigated plots. The CFE actually increased after rewetting in the ﬁrst two irrigations but not in the third event, suggesting that the capacity of the soil to release labile organic C from soil aggregates or litter was reduced after each irrigation event. Overall, the C released as CO2 in the ﬁrst 24 h was related to the CFE existing before rewetting, which may help to explain the spatial variability in SR. However, the explained variability decreased after each irrigation, suggesting a change to a less labile composition of the CFE fraction as a consequence of multiple drying-rewetting cycles
Keywords: Chloroform-fumigation K2SO4-extraction; drying-rewetting cycles; holm oak savanna woodland; Soil C fractions; Soil respiration

Litter decomposition and faunal activity in Mediterranean forest soils: effects of N content and the moss layer - Garcia-Pausas, Jordi; Casals, Pere; Romanyà, Joan (Soil Biology and Biochemistry, 2004)
Accumulation of soil carbon is mainly controlled by the balance between litter production and litter decomposition. Usually In Mediterranean forests there are contrasting conditions in the distribution of faunal activity and the moss layer that may have different effects on litter decomposition. Decomposition and faunal activity were studied by exposing litter of contrasting quality (Pinus halepensis Mill. and Quercus ilex L.) for 3.5 yr in three Mediterranean pine forests of the eastern Iberian Peninsula. The effects of mosses on decomposition and on faunal activity were studied by exposing P. halepensis litter either on moss patches or directly on the forest ﬂoor. Faecal pellet production was used as an indication of faunal activity. Water availability or soil characteristics seem to limit faunal activities in the drier sites. Faecal pellets were not found during the ﬁrst stages of decomposition and in all sites they appeared when about a 30% of the initial litter had decomposed. Under wet conditions faecal pellet production was very high and a mass balance suggested that soil faunal activity may result in a net ﬂow of organic matter from the lower organic horizons to the surface Oi horizon. Mosses slightly increased mass loss of pine litter probably as a consequence of high potentially mineralizable nitrogen in the Oa horizon of moss patches and also, perhaps, as a consequence of the higher moisture content measured in the Oi horizon needles sampled among the mosses. In contrast, moss patches reduced faunal activity. The effect of litter quality on mass loss was not always signiﬁcant, suggesting an interaction between litter quality and site conditions. During the ﬁrst stages of decomposition there was N immobilisation in P. halepensis litter (poorer in N) and N release from Q. ilex litter (richer in N). In conclusion, in these forests soil microclimate and/or N availability appear to be more important controlling litter decomposition than the distribution of faunal activity.
Keywords: faecal pellets; litter decomposition; litter n content; Mediterranean forests; moss layer; nitrogen dynamics

Litter decomposition and faunal activity in Mediterranean forest soils: effects of N content and the moss layer - Garcia-Pausas, Jordi; Casals, Pere; Romanyà, Joan (Soil Biology and Biochemistry, 2004)
Accumulation of soil carbon is mainly controlled by the balance between litter production and litter decomposition. Usually In Mediterranean forests there are contrasting conditions in the distribution of faunal activity and the moss layer that may have different effects on litter decomposition. Decomposition and faunal activity were studied by exposing litter of contrasting quality (Pinus halepensis Mill. and Quercus ilex L.) for 3.5 yr in three Mediterranean pine forests of the eastern Iberian Peninsula. The effects of mosses on decomposition and on faunal activity were studied by exposing P. halepensis litter either on moss patches or directly on the forest ﬂoor. Faecal pellet production was used as an indication of faunal activity. Water availability or soil characteristics seem to limit faunal activities in the drier sites. Faecal pellets were not found during the ﬁrst stages of decomposition and in all sites they appeared when about a 30% of the initial litter had decomposed. Under wet conditions faecal pellet production was very high and a mass balance suggested that soil faunal activity may result in a net ﬂow of organic matter from the lower organic horizons to the surface Oi horizon. Mosses slightly increased mass loss of pine litter probably as a consequence of high potentially mineralizable nitrogen in the Oa horizon of moss patches and also, perhaps, as a consequence of the higher moisture content measured in the Oi horizon needles sampled among the mosses. In contrast, moss patches reduced faunal activity. The effect of litter quality on mass loss was not always signiﬁcant, suggesting an interaction between litter quality and site conditions. During the ﬁrst stages of decomposition there was N immobilisation in P. halepensis litter (poorer in N) and N release from Q. ilex litter (richer in N). In conclusion, in these forests soil microclimate and/or N availability appear to be more important controlling litter decomposition than the distribution of faunal activity.
Keywords: faecal pellets; litter decomposition; litter n content; Mediterranean forests; moss layer; nitrogen dynamics